Sexuality and deafness: a dialogue from Michel Foucault (Research, Society and Development, 2022)
This article aims to develop a problematization of issues related to the deaf person's sexuality from the perspective of Foucault's studies. Therefore, a literature review of a qualitative nature was carried out. The research resorted to an investigation of the bases in the Capes Journal Portal - theses and dissertations, in the Scientific Electronic Library Online – Scielo and Academic Google, with a time frame over the last eleven years (2010-2021). In total, only one study was identified that investigates the same strand proposed in this study. In short, it was noticed that the sexuality of deaf people is still treated from a biological perspective, in a prescriptive and regulatory way, in which subjects are referred to as incapable of receiving information and experiencing affective and erotic relationships in their daily lives. Furthermore, the inexistence of studies dealing with the theme was evidenced, which confirms the need to systematize research in this area, with the aim of providing advances in Foucault's work on the sexuality of the deaf community. Keywords: Sexuality; Deafness; Michel Foucault, Research In Education.